Laboratory Studies on the Release of Cations and Anions in Acid Sulfate Soils from Pulau Lumut,Selangor - Jusop, Shamsuddin; A. Auxtero, Edgardo (1991)
Acid sulfate soils in Peninsular Malaysia are characterized l7y low pH and high amounts of At. Alleviation of toxic ions in the soils l7y controlled drainage is recommended. However, potential acidity remains in the soils due to slow release of toxic ions during mineral weathering. A study was conducted to determine the release of Al and other ions l7y repetitive extraction of samples from the field and l7y aerobic incubation of samples in the laboratory. The results showed that Al was released continuously from the soils even after the sixth extraction. When the soils were allowed to undergo free oxidation under aerobic conditions Al, Mn, Fe, Ca, Mg, K, Na and S were released into the soil solutions due to breakdown of clay minerals. Activities of these ions increased significantly, resulting in an increase of electrical conductivity of the soil solution. Additionally, pH of the soil solution dropped. These commonly observed properties of acid sulfate soils have great implications on their management practices.